PecS Is a Global Regulator of the Symptomatic Phase in the Phytopathogenic Bacterium Erwinia chrysanthemi 3937 - Hommais, Florence; Oger-Desfeux, Christine; Van Gijsegem, Frédérique; Castang, Sandra; Ligori, Sandrine; Expert, Dominique; Nasser, William; Reverchon, Sylvie (Journal of Bacteriology, 2008)
Article Usage Stats Services JB Citing Articles Google Scholar PubMed Related Content Social Bookmarking CiteULike Delicious Digg Facebook Google+ Mendeley Reddit StumbleUpon Twitter current issue JB About JB Subscribers Authors Reviewers Advertisers Inquiries from the Press Permissions & Commercial Reprints ASM Journals Public Access Policy JB RSS Feeds 1752 N Street N.W. • Washington DC 20036 202.737.3600 • 202.942.9355 fax • journals@asmusa.org Print ISSN: 0021-9193 Online ISSN: 1098-5530 Copyright © 2014 by the American Society for Microbiology. For an alternate route to JB .asm.org, visit: JB